Sunteți pe pagina 1din 5

Exercise 6.

11 (Solutions)

mathcity.org

Textbook of Algebra and Trigonometry for Class XI

Merging man and maths

Available online @ http://www.mathcity.org, Version: 1.0.0

Formula for the sum

n ( n + 1)
2
k =1
n
n ( n + 1)( 2n + 1)
k 2 = 12 + 22 + 32 + ......... + n 2 =

6
k =1
n

i)
ii)

= 1 + 2 + 3 + ......... + n =

n ( n + 1)
k
=
1
+
2
+
3
+
.........
+
n
=

k =1
2
n

iii)

iv)

(1) =

1 + 1 + 1 + ......... + 1 (n times) = n

k =1

Question # 1
1 1 + 2 4 + 3 7 + ..........................
If Tk denotes the kth term of the series then

Tk = k (3k 2) = 3k 2 2k
Let S n denotes the sum of first n terms of the series then
n

S n = 3k 2 2k
k =1
n

1 + (k 1)3
= 1 + 3k 3
= 3k 2

n
n(n + 1)(2 n + 1) n(n + 1)
= 3 k 2 2 k = 3
2

2
k =1
k =1
n(n + 1)(2n + 1)
=
n(n + 1)
2
n(n + 1)
n(n + 1)(2n 1)
=
Answer
( 2n + 1 2 ) =
2
2

Question # 2
1 3 + 3 6 + 5 9 + .........................
If Tk denotes the kth term of the series then

Tk = (2k 1)(3k ) = 6k 2 3k
Now do yourself as above.

1 + (k 1)2
= 1 + 2k 2
= 2k 1
3 + ( k 1)3
= 3 + 3k 3
= 3k

Question # 3 & 4
Do yourself as Question # 1
Question # 5
12 + 32 + 52 + ....................
If Tk denotes the kth term of the series then

Tk = (2k 1)2 = 4k 2 4k + 1
Let S n denotes the sum of first n terms of the series then
n

1 + ( k 1)2
= 1 + 2k 2
= 2k 1

S n = 4k 2 4k + 1
k =1
n

n
n
n(n + 1)(2n + 1)
n(n + 1)
= 4 k 2 4 k + (1) = 4
4
+n
6
2

k =1
k =1
k =1
2n(n + 1)(2 n + 1)
=
2 ( n(n + 1) ) + n
3

FSc-I / 6.11 -2

2(2n 2 + 2n + n + 1)

2(n + 1)(2n + 1)

= n
2(n + 1) + 1 = n
2n 2 + 1
3
3

2(2n 2 + 3n + 1)

4n 2 + 6n + 2 6n 3
= n
2n 1 = n

3
3

4n 2 1 n
2
= n
= ( 4n 1)
3 3

Answer

Question # 6
2 2 + 52 + 82 + ....................
Let S n denotes the sum of first n terms of the series then

2 + ( k 1)3
= 2 + 3k 3
= 3k 1

Tk = (3k 1)2 = 9k 2 6k + 1
Let S n be the sum of first n term of the series then
Now do yourself as above
Question # 7
2 12 + 4 22 + 6 32 + ...................
If Tk denotes the kth term of the series then

2 + ( k 1)2
= 2 + 2k 2
= 2k

Tk = (2k )(k ) 2 = 2k 3
Let S n denotes the sum of first n terms of the series then
n

S n = (2k ) = 2 k 3

1 + (k 1)1
= 1+ k 1
=k

k =1

k =1
2

n 2 (n + 1)2 n 2 (n + 1) 2
n(n + 1)
= 2
=
=2
4
2
2

Answer

Question #8
3 22 + 5 32 + 7 42 + ...................
If Tk denotes the kth term of the series then

Tk = (2k + 1)(k + 1)2 = (2k + 1)(k 2 + 2k + 1)


= 2k 3 + 4k 2 + 2k + k 2 + 2k + 1
= 2k 3 + 5k 2 + 4k + 1
Let S n denotes the sum of first n terms of the series then
n

S n = (2k 3 + 5k 2 + 4k + 1)
k =1
n

k =1

k =1

= 2 k + 5 k + 4 k + (1)
3

k =1

k =1
2

n(n + 1)
n(n + 1)
n(n + 1)(2n + 1)
= 2
+n
+ 5
+4
6
2
2

n 2 (n + 1)2 5n (n + 1)(2n + 1)
=2
+
+ 2n(n + 1) + n
4
6
n(n 2 + 2n + 1) 5(2n 2 + 2n + n + 1)

= n
+
+ 2(n + 1) + 1
2
6

n 3 + 2n 2 + n 5(2n 2 + 3n + 1)

= n
+
+ 2n + 2 + 1
2
6

3 + ( k 1)2
= 3 + 2k 2
= 2k + 1
2 + (k 1)1
= 2 + k 1
= k +1

FSc-I / 6.11 -3

n 3 + 2n 2 + n 10 n 2 + 15n + 5

= n
+
+ 2n + 3
2
6

3n3 + 6 n 2 + 3n + 10n 2 + 15n + 5 + 12n + 18


= n

n
= ( 3n3 + 16n 2 + 30n + 23 ) Answer
6
Question # 9
2 4 7 + 3 6 10 + 4 8 13 + ......................
If Tk denotes the kth term of the series then

2 + (k 1)1
= 2 + k 1
= k +1
7 + ( k 1)3
= 7 + 3k 3
= 3k + 4

Tk = 2(k + 1)(k + 1)(3k + 4) = 2(k + 1)2 (3k + 4)


= 2(k 2 + 2k + 1)(3k + 4)
= 3k 3 + 6k 2 + 3k + 4k 2 + 8k + 4
= 3k 3 + 10k 2 + 11k + 4
Now do yourself.

4 + ( k 1)2
= 4 + 2k 2
= 2 k + 2 = 2( k + 1)

Question # 10
1 4 6 + 4 7 10 + 7 10 14 + ...................
If Tk denotes the kth term of the series then
Tk = (3k 2)(3k + 1) 2(2k + 1) = 2(3k 2)(3k + 1)(2k + 1)

= 2(3k 2)(6k + 2k + 3k + 1) = 2(3k 2)(6k + 5k + 1)


= 2(18k 3 + 15k 2 + 3k 12k 2 10k 2)
= 2(18k 3 + 3k 2 7k 2)
Now do yourself.
2

Question # 11
1 + (1 + 2) + (1 + 2 + 3) + ......................
If Tk denotes the kth term of the series then
k ( k + 1) 1 2
Tk = 1 + 2 + 3 + ........... + k =
= (k + k )
2
2
Let S n denotes the sum of first n terms of the series then
n
1 2
1 n 2 1 n
Sn = (k + k ) = k + k
2 k =1
2 k =1
k =1 2
1 n(n + 1)(2n + 1) 1 n(n + 1)
=
+

2
6
2 2
n(n + 1) (2n + 1) n(n + 1) 2n + 1 + 3
=
+ 1 =

4 3
4
3

n(n + 1) 2n + 4 n(n + 1)(2n + 4)


=
Answer

=
4 3
12
Question # 12
12 + (12 + 22 ) + (12 + 22 + 32 ) + .................
If Tk denotes the kth term of the series then
k ( k + 1)( 2k + 1)
Tk = 12 + 2 2 + 32 + ........... + k 2 =
6
1
1
= k ( 2k 2 + 2k + k + 1) = k ( 2k 2 + 3k + 1)
6
6

1 + ( k 1)3
= 1 + 3k 3
= 3k 2
4 + ( k 1)3
= 4 + 3k 3
= 3k + 1
6 + ( k 1)4
= 6 + 4k 4
= 4k + 2 = 2(2k + 1)

FSc-I / 6.11 -4

1
1
1
1
2 k 3 + 3k 2 + k ) = k 3 + k 2 + k
(
6
3
2
6
Let S n denotes the sum of first n terms of the series then
n
1 3 1 2 1 1 n 3 1 n 2 1 n
Sn = k + k + k = k + k + k
2
6 3 k =1
2 k =1
6 k =1
k =1 3
1 n 2 (n + 1)2 1 n (n + 1)(2n + 1) 1 n(n + 1)
=
+
+

3
4
2
6

6 2

n(n + 1)
n(n + 1) 2
=
n + n + 2n + 1 + 2
( n(n + 1) + (2n + 1) + 1) =
12
12
n(n + 1)(n 2 + 3n + 3)
=
Answer
12
=

Question # 13
2 + (2 + 5) + (2 + 5 + 8) + ....................
n
If Tk denotes the kth term of the series then
Q S n = [ 2a1 + ( n 1)d ]
2
Tk = 2 + 5 + 8 + ........... + up to k terms
k
k
k
3
1
= [ 2(2) + (k 1)(3)] = [ 4 + 3k 3] = [3k + 1] = k 2 + k
2
2
2
2
2
Now do yourself
Question # 14 (i)
12 22 + 32 42 + ............. + (2n 1)2 (2n)2
If Tk denotes the kth term of the series then

Tk = (2k 1)2 (2k ) 2 = 4k 2 4k + 1 4k 2 = 4k + 1


Now do yourself
Question # 14 (ii)
12 32 + 52 72 + ............. + (4n 3)2 (4n 1) 2
If Tk denotes the kth term of the series then

Tk = (4k 3)2 (4k 1) 2 = (16k 2 24k + 9) (16k 2 8k + 1)


= 16k 2 24k + 9 16k 2 + 8k 1 = 16k + 8
Now do yourself
Question # 14 (iii)
12 12 + 22 12 + 2 2 + 32
+
+
+ ....................... to n terms
1
2
3
If Tk denotes the kth term of the series then
12 + 22 + 32 + ............ + k 2
Tk =
k
k (k + 1)(2k + 1)
6 = k (k + 1)(2k + 1) = (k + 1)(2k + 1)
=
k
6k
6
2
2
2k + 2 k + k + 1 2k + 3k + 1 2 2 3
1
=
=
= k + k+
6
6
6
6
6
1
1
1
= k2 + k +
3
2
6
Let S n denotes the sum of first n terms of the series then
n
1 1 n 2 1 n
1 n
1 2 1
S n = k + k + = k + k + (1)
2
6 3 k =1
2 k =1
6 k =1
k =1 3

FSc-I / 6.11 -5

1 n(n + 1)(2n + 1) 1 n(n + 1) n


=
+
+
3
6
2 2 6
n(n + 1)(2n + 1) n (n + 1) n n (n + 1)(2n + 1) n + 1 1
=
+
+ =
+
+
18
4
3 2
9
2
3
n (2n 2 + 2n + n + 1) n + 1 1 n 2n 2 + 3n + 1 n + 1 1
=
+
+ =
+
+
2
9
2
3 2
9
2
3
n 4n 2 + 6n + 2 + 9n + 9 + 6 n 4n 2 + 15n + 17
=
=

2
18
18
2

n
= ( 4n 2 + 15n + 17 ) Answer
36
Question # 15 (i)
Since Tn = 3n 2 + n + 1
Therefore Tk = 3k 2 + k + 1
Now do yourself
Question # 15 (ii)
Do yourself
Question # 16 (i)
Do yourself as below ( Q # 16 (ii) )
Question # 16 (ii)
Since Tn = n3 + 2n + 3
Therefore Tk = k 3 + 2k + 3
Let S n denotes the sum of first n terms of the series then
n

k =1

k =1

k =1

S n = k 3 + 2k + 3 = k 3 + 2 k + 3 (1)
k =1

n(n + 1)2

n (n + 1)
n(n + 1)
+2
+ 3n = n
+ n +1 + 3
4
2
4

n(n 2 + 2n + 1)

n 3 + 2n 2 + n

= n
+ n + 4 = n
+n + 4
4
4

3
2
n + 2n + n + 4n + 16
= n

n
= n 3 + 2n 2 + 5n + 16
4
Now for sum of first 2n terms put n = 2n
2n
S2n =
(2n)3 + 2(2n) 2 + 5(2n) + 16
4
n
2n
= 8n3 + 8n 2 + 10n + 16 =
4n3 + 4 n 2 + 5n + 8
2
2
3
2
= n ( 4n + 4n + 5n + 8 ) Answer

Made By Atiq ur Rehman ( atiq@mathcity.org ), http://www.mathcity.org